Deadbeat control for a single-phase cascaded H-bridge rectifier with voltage balancing modulation - Qi, Chen (2018)
The model predictive control (MPC) is a promising control method for cascaded H-bridge (CHB) rectifiers. One well-known MPC method is the finite-control-set MPC (FCS-MPC). However, three main issues arise in FCS-MPC: heavy computational burden, low steady-state performance, and time-consuming tuning work of weighting factor. Here, an alternative MPC method, deadbeat (DB) control with a capability of voltage balance, has been proposed for a single-phase CHB rectifier. The proposed method is based on the DB solution to obtain zero current error at the sampling instant and the use of a redundancy-based modulation strategy for voltage balance, leading to the ease of controller design and elimination of tuning work. The proposed method has been evaluated against FCS-MPC method on a single-phase three-cell CHB rectifier. The experimental results show that a reduced computational burden, an improved steady-state performance, and a comparable dynamic response can be achieved in the proposed method in comparison with FCS-MPC method.